Targeting obesity management through gut microbiota modulation by herbal products: A systematic review. (February 2019) - Ejtahed, Hanieh-Sadat; Soroush, Ahmad-Reza; Siadat, Seyed-Davar; Hoseini-Tavassol, Zahra; Larijani, Bagher; Hasani-Ranjbar, Shirin
Highlights: Herbal products consumption might have beneficial effects on restoring healthy gut microbiome. The baseline composition of gut microbiota has effects on alteration of gut microbiota after interventions. Short chain fatty acids including acetic, propionic and butyric acids as microbiota-derived metabolites have effects on host physiology. Abstract: Objectives: The gut dysbiosis has been implicated as a mediator to obesity and its manipulation could be an appropriate approach to sustainable weight loss. In this systematic review, our primary objective was to assess the potential manipulation of gut microbiota by herbal products in obesity. Materials and methods: We did a comprehensive search in PubMed, Web of Science, Scopus and Cochrane databases for all clinical trials and animal studies exploring the effects of various herbal products on gut microbiota composition in obesity documented up to May 2017. Results: Our initial search yielded 2766 articles. After screening abstracts and full texts, 68 articles were included (55 animal studies and 13 clinical trials). The studies differed in their methodologies, type of interventions and intervention lengths. The weight loss was only reported in 23% of trials and in 64% of animal studies. An increasing tendency in Bifidobacterium species and butyrate-producing bacteria such as Faecalibacterium prausnitzii were observed after consuming non-digestible carbohydrates, although these changes did not always correlate with weight loss. Supplementation with high concentration of polyphenols reduced body weight gain in animal studies and inhibited growth of detrimental species such as Clostridia and Enterobacteria while the growth of Lactic acid bacteria and Akkermansia muciniphila is enriched. Conclusions: Alteration of gut microbiota after interventions has been affected by the baseline composition of gut microbiota. This systematic review shows that consumption of herbal products might have beneficial effects on restoring healthy gut microbiome besides body fat reduction.